"Just because people are old, just because they're ill…" dignity matters in district nursing. Issue 1 (20th December 2021) - Stevens, Emma; Price, Liz; Walker, Liz
Abstract : Purpose: This paper aims to explore the concept and practice, of dignity as understood and experienced by older adults and district nursing staff. The paper adds a new, nuanced, understanding of safeguarding possibilities in the context of district nursing care delivered in the home. Design/methodology/approach: The research used an ethnographic methodology involving observations of care between community district nursing clinicians and patients (n = 62) and semi-structured interviews with nursing staff (n = 11) and older adult recipients of district nursing care (n = 11) in England. Findings: Abuse is less likely to occur when clinicians are maintaining the dignity of their patients. The themes of time and space are used to demonstrate some fundamental ways in which dignity manifests. The absence of dignity offers opportunities for abuse and neglect to thrive; therefore, both time and space are essential safeguarding considerations. Dignity is influenced by time and how it is experienced temporally, but nurses are not allocated time to "do dignity", an arguably essential component of the caregiving role, yet one that can become marginalised. The home-clinic exists as a clinical space requiring careful management to ensure it is also an environment of dignity that can safeguard older adults. Practical implications: District nurses have both a proactive and reactive role in ensuring their patients remain safeguarded. By ensuring care is delivered with dignity and taking appropriate action if they suspect abuse or neglect, district nurses can safeguard their patients. Originality/value: This paper begins to address an omission in existing empirical research regarding the role of district nursing teams in delivering dignified care and how this can safeguard older adults.